1996
DOI: 10.1117/12.241251
|View full text |Cite
|
Sign up to set email alerts
|

<title>Improved landmine detection capability (ILDC): systematic approach to the detection of buried mines using passive IR imaging</title>

Abstract: In order to reduce the serious problem associated with the mining of important supply/communication roads by hostile parties during peacekeeping operations, the Canadian Department of National Defence has recently begun the development of a multi-sensor teleoperated mine detection vehicle, the Improved Landmine Detection Capability (ILDC) . One sensor identified as a serious candidate for that project is a passive IR camera. In the past, many organizations have assessed the efficiency of this technique of dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…These papers indicate that a typical value for both the characteristic dimension of the discontinuity and its depth beneath the surface will be less than 0.01 m. For the discontinuities detected, the ratio of depth to characteristic dimension rarely exceeds 0.7. Maierhofer et al [3] also used this technique to detect voids in a concrete block where both the characteristic dimension and burial depth of the discontinuity were an order of magnitude greater than those described by Almond et al When this procedure is applied to the detection of landmines, the discontinuity within the homogeneous soil is taken to be either the complete landmine [4,5], an internal component of the mine such as the gas space used to house its firing mechanism [6,7] or possibly even the disturbed soil created when the mine was buried [8]. Most of these discontinuities have a similar location: the upper surface of the mine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These papers indicate that a typical value for both the characteristic dimension of the discontinuity and its depth beneath the surface will be less than 0.01 m. For the discontinuities detected, the ratio of depth to characteristic dimension rarely exceeds 0.7. Maierhofer et al [3] also used this technique to detect voids in a concrete block where both the characteristic dimension and burial depth of the discontinuity were an order of magnitude greater than those described by Almond et al When this procedure is applied to the detection of landmines, the discontinuity within the homogeneous soil is taken to be either the complete landmine [4,5], an internal component of the mine such as the gas space used to house its firing mechanism [6,7] or possibly even the disturbed soil created when the mine was buried [8]. Most of these discontinuities have a similar location: the upper surface of the mine.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these discontinuities have a similar location: the upper surface of the mine. The heating process adopted for mine detection schemes include the surface heating of the soil using infrared lamps [4,9], solar energy [6,8,10,11] and the volumetric heating of the soil by microwave energy [7,12]. Each of these heating processes introduces features which can assist or limit the overall detection process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the update rules in (71) and (72), it can be shown that the weights need to be updated using: (80) where…”
Section: H Mcfjgpd Based Methodsmentioning
confidence: 99%
“…When it is due primarily to the disturbed soil layer above and around the mine (resulting from the burying operation), one speaks of a surface effect, which can be detectable for some time (say weeks) after burial and enhances the mine's signature. A good explanation of the various thermal mechanisms affecting the surface temperature contrast can be found in [109].…”
Section: Infrared Imaging Or)mentioning
confidence: 99%